Position paper of the Cardiovascular Committee of the European Association of Nuclear Medicine (EANM) on PET imaging of atherosclerosis - Bucerius, Jan; Hyafil, Fabien; Verberne, Hein J.; Slart, Riemer H. J. A.; Lindner, Oliver; Sciagra, Roberto; Agostini, Denis; Übleis, Christopher; Gimelli, Alessia; Hacker, Marcus (European journal of nuclear medicine and molecular imaging, 2016)
Cardiovascular diseases are the leading cause of death not only in Europe but also in the rest of the World. Preventive measures, however, often fail and cardiovascular disease may manifest as an acute coronary syndrome, stroke or even sudden death after years of silent progression. Thus, there is a considerable need for innovative diagnostic and therapeutic approaches to improve the quality of care and limit the burden of cardiovascular diseases. During the past 10 years, several retrospective and prospective clinical studies have been published using 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) to quantify inflammation in atherosclerotic plaques. However, the current variety of imaging protocols used for vascular (arterial) imaging with FDG PET considerably limits the ability to compare results between studies and to build large multicentre imaging registries. Based on the existing literature and the experience of the Members of the European Association of Nuclear Medicine (EANM) Cardiovascular Committee, the objective of this position paper was to propose optimized and standardized protocols for imaging and interpretation of PET scans in atherosclerosis. These recommendations do not, however, replace the individual responsibility of healthcare professionals to make appropriate decisions in the circumstances of the individual study protocols used and the individual patient, in consultation with the patient and, where appropriate and necessary, the patient’s guardian or carer. These recommendations suffer from the absence of conclusive evidence on many of the recommendations. Therefore, they are not intended and should not be used as "strict guidelines" but should, as already mentioned, provide a basis for standardized clinical atherosclerosis PET imaging protocols, which are subject to further and continuing evaluation and improvement. However, this EANM position paper might indeed be a first step towards "official" guidelines on atherosclerosis imaging with PET.